IMPLEMENTATION OF MANAGEMENT OF ZAKAT COLLECTING UNIT (UPZ) IN IMPROVING THE ECONOMY OF ISLAMIC COMMUNITY IN MARGAHARJA-SUKADANA VILLAGE, CIAMIS REGENCY - Aan Andriawan; Hasan Bisri; Daryaman Daryaman (Syari'ah Economics, 2022)
This study aims to determine the planning, implementation, and management results of the Margaharja Zakat Collecting Unit (UPZ) Sukadana District. However, the main objective of this study is to determine the economic improvement of the Islamic community through the Zakat Collecting Unit (UPZ). The research method used is a qualitative method, namely identifying the state of an object or event to draw conclusions that apply in general by using descriptive analysis techniques. Data were collected by observation, interviews, and document studies. The study results show that the management implementation of the Margaharja Zakat Collecting Unit (UPZ) has been going well. In terms of planning and also its performance by creating success in increasing the satisfaction of zakat givers. This village's Zakat Collecting Unit (UPZ) has also improved the community's economy. It has a real positive impact because the distribution of zakat is in the form of working capital, not consumption goods.